Selection of Quantum Dot Wavelengths for Biomedical Assays and Imaging - Yong Taik Lim; Sungjee Kim; Akira Nakayama; Nathan E. Stott; Moungi G. Bawendi; John V. Frangioni (Molecular Imaging)
Fluorescent semiconductor nanocrystals (quantum dots [QDs]) are hypothesized to be excellent contrast agents for biomedical assays and imaging. A unique property of QDs is that their absorbance increases with increasing separation between excitation and emission wavelengths. Much of the enthusiasm for using QDs in vivo stems from this property, since photon yield should be proportional to the integral of the broadband absorption. In this study, we demonstrate that tissue scatter and absorbance can sometimes offset increasing QD absorption at bluer wavelengths, and counteract this potential advantage. By using a previously validated mathematical model, we explored the effects of tissue absorbance, tissue scatter, wavelength dependence of the scatter, water-to- hemoglobin ratio, and tissue thickness on QD performance. We conclude that when embedded in biological fluids and tissues, QD excitation wavelengths will often be quite constrained, and that excitation and emission wavelengths should be selected carefully based on the particular application. Based on our results, we produced near-infrared QDs optimized for imaging surface vasculature with white light excitation and a silicon CCD camera, and used them to image the coronary vasculature in vivo. Taken together, our data should prove useful in designing fluorescent QD contrast agents optimized for specific biomedical applications.